The Role of Religion and Spirituality in Managing Residual Schizophrenia: Article Review - Al Hajiri, Aufar Zimamuz Zaman; AS, Nur Azizah; Algristian, Hafid (Jurnal Medis Islam Internasional, 2021)
Background: Residual Schizophrenia is a chronic condition of schizophrenia characterized by a history of leastwise one psychotic episode with more prominent negative symptoms. Schizophrenic patients who have persistent psychotic symptoms and patients with residual schizophrenia should receive adequate pharmacotherapy, and may consider additional cognitive therapy, as it has been shown to help reduce relapse rates, reduce psychotic symptoms, and improve or stabilize the patient's mental state. Objective: To determine the role of religion and spirituality in the management of patients with residual schizophrenia.Methods: The design of this research is a literature review or library review, which is a systematic, direct, and reproducible research method by identifying, evaluating, and synthesizing published research.Result: Patients with a higher level of religion or spirituality or their strong personal belief system are more likely to use positive appraisal to deal with their illness or problem which includes giving positive meaning to the situation and being optimistic. Conclusion: The presence of religion and spirituality help the coping mechanisms of residual Schizophrenia patients which also improves patient management, accelerate the healing process, and increases QOL of patients. Keywords: Spirituality, Religion, Residual Schizophrenia.